Ensuring assembling accuracy with thermal influence of multi-element connection - Черкашина, Ольга Сергіївна (Eastern-European Journal of Enterprise Technologies, 2013)
The quality of production depends on supporting the regulatory framework of the product output at all stages of production life cycle. The paper is devoted to ensuring the accuracy of assembling with thermal influence of multi-element connections due to the calculation of dimensional accuracy at the stage of technological preparation of production with regard to expansion gaps formed by heating and assembling the elements of products. The analysis of processes, that take place under the thermal influence at the point of contact of mounting surface of multi-element connection components, was performed, mathematical simulation of the product thermal state was carried out and the regularity of expansion gap change was determined using the existing systems of computer-aided engineering analysis. Based on the analysis an improved formula for calculating the dimensional accuracy of assembling was obtained and a classification of the bush-type parts with models of determining expansion gaps, included in the calculation, was proposed.